2015
DOI: 10.1371/journal.pone.0133525
|View full text |Cite|
|
Sign up to set email alerts
|

Glyphosate Use Predicts ADHD Hospital Discharges in the Healthcare Cost and Utilization Project Net (HCUPnet): A Two-Way Fixed-Effects Analysis

Abstract: There has been considerable international study on the etiology of rising mental disorders, such as attention-deficit hyperactivity disorder (ADHD), in human populations. As glyphosate is the most commonly used herbicide in the world, we sought to test the hypothesis that glyphosate use in agriculture may be a contributing environmental factor to the rise of ADHD in human populations. State estimates for glyphosate use and nitrogen fertilizer use were obtained from the U.S. Geological Survey (USGS). We queried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Additional studies also reported a particular role of exposure to the agricultural and combustion pollutant, nitrous oxide (N 2 O), which might be a primary environmental trigger in the onset of not only ADHD but also of other neurodevelopmental disorders, such as ASD. On this particular aspect of agricultural pollutants, glyphosate could also be a factor responsible for ADHD [ 413 ].…”
Section: Pathologiesmentioning
confidence: 99%
“…Additional studies also reported a particular role of exposure to the agricultural and combustion pollutant, nitrous oxide (N 2 O), which might be a primary environmental trigger in the onset of not only ADHD but also of other neurodevelopmental disorders, such as ASD. On this particular aspect of agricultural pollutants, glyphosate could also be a factor responsible for ADHD [ 413 ].…”
Section: Pathologiesmentioning
confidence: 99%
“…Unfortunately, editors seem often unaware of the problem that more and more non-scientists try to publish allegedly scientific studies in scientific journals. In this context, a mistakenly published study is noteworthy that linked the most commonly used herbicide glyphosate to the rise of ADHD (Fluegge and Fluegge 2015). This paper was rejected after peer review and consultation with the editorial board of PLoS ONE (The PLoS ONE staff 2015).…”
mentioning
confidence: 99%
“…bodies of water) in southern Minnesota (USA) have reported levels that are significantly higher than established Intergovernmental Panel on Climate Change estimates [7], suggesting that a more comprehensive reevaluation of environmental N 2 O burden is warranted. Interestingly, obesity rates are climbing significantly in states with large agricultural operations [9], and perhaps more importantly, a recent epidemiological study on ADHD (case discernment derived from inpatient psychiatric evaluation, and therefore representing possible 'severe' ADHD) indicated that the highest ADHD prevalence occurred in the states of Nebraska and Minnesota [10,11].…”
mentioning
confidence: 99%
“…In accord with the literature identifying ADHD symptoms in children exposed to general anesthesia for surgery [12], it has been proposed that increasing exposure to environmental N 2 O-most especially in light of a marked reduction in other air pollutants [13]-may be the principal exposure contributing to ADHD and other neurodevelopmental pathologies, like autism spectrum disorders (ASD). [10,11,14,15] Through targeting several neural substrates, including those of the opioidergic, cholinergic, dopaminergic, and glutamatergic systems, this exposure may cumulatively induce a chronic parasympathetic state in those exposed [15], as has been shown in healthy humans exposed to inhalational N 2 O [16]. Given that environmentally relevant concentrations (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation